Thermal Shock Study on Different Advanced Ceramics by Laser Irradiation in Different Media. Issue 1 (12th June 2015) - Pulz, Robert; Rehmer, Birgit; Schneider, Gerold A.; Skrotzki, Birgit
Abstract : The thermal shock behavior of three commercial‐advanced ceramics (SSiC, MgO–PSZ, Al2 O3 ) is characterized in air and vacuum applying a laser thermal shock. The available testing system permits the reproducible setting of defined temperature profiles in thin disks and allows a heating‐up thermal shock in various media. Due to the accurate determination of the time‐ and space‐resolved temperature distribution, the local stress state can be calculated as a function of time. It is shown that the thermal shock strength is highest for SSiC and lowest in Al2 O3 with MgO–PSZ in between. The approach presented in this work allows quantifying the stress state at failure in terms of tangential tensile stress. The investigated environment does not affect the thermal shock resistance under the studied experimental conditions. Abstract : The thermal shock behavior of three ceramics is characterized applying a heating‐up laser thermal shock. The time‐ and space‐resolved measurement of the temperature distribution allows the calculation of the local stress state as a function of time. The thermal shock strength is highest for SSiC and lowest in Al2 O3 with MgO–PSZ in between. The investigated environment does not affect the thermal shock resistance under the studied experimental conditions.